The Role of the Business Environment in Improving the Competitiveness of the West Java Traditional Medicine Industry - Elan Eriswanto; Antony Antony (Universitas Mercu Buana, 2025)
Objectives: This study aims to analyze the role of the business environment in improving the competitiveness of the traditional medicine industry in West Java by identifying business environment factors that affect competitiveness and measuring the significance of the influence of each factor.Methodology: The research used a mixed method approach with explanatory sequential design. Quantitative data collection was conducted through a structured survey of 222 traditional medicine businesses in West Java selected by stratified random sampling based on business scale and geographical area. Qualitative data were obtained through in-depth interviews and focus group discussions with 18 key informants. Data analysis used multiple regression, structural equation modeling (SEM), and ANOVA, integrated with content analysis for qualitative data.Finding: The results showed that seven dimensions of the business environment significantly influenced the competitiveness of the traditional medicine industry with a value of R² = 0.613. Market access (β = 0.312) and technology and innovation (β = 0.286) are the most dominant factors, while raw material availability has the highest perception (mean = 3.87). There were significant gaps in technology and innovation (mean = 2.65) and access to finance (mean = 2.78). ANOVA analysis showed significant differences in competitiveness levels based on enterprise scale (F = 18.653, p < 0.01), with larger-scale enterprises showing higher competitiveness.Conclusion: The business environment plays an important role in improving the competitiveness of the traditional medicine industry in West Java. A holistic approach is needed in developing a conducive business environment, including simplifying regulations, strengthening the innovation ecosystem, developing market access, and special financing schemes to encourage the transformation of the traditional medicine industry towards a more modern and globally competitive industry. An integrated and ecosystem-based industrial development approach is key to improving the competitiveness and sustainability of this industry in the long term.